2013
DOI: 10.1155/2013/524625
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Gas Exchange and Nutrient Use Efficiency Help Explain the Distribution of Two Neotropical Mangroves under Contrasting Flooding and Salinity

Abstract: Rhizophora mangleandLaguncularia racemosacooccur along many intertidal floodplains in the Neotropics. Their patterns of dominance shift along various gradients, coincident with salinity, soil fertility, and tidal flooding. We used leaf gas exchange metrics to investigate the strategies of these two species in mixed culture to simulate competition under different salinity concentrations and hydroperiods. Semidiurnal tidal and permanent flooding hydroperiods at two constant salinity regimes (10 g L−1and 40 g L−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, those differences disappear if the amount of N invested in glycinebetain is subtracted from the total amount of N. In both species, the NUE decreases in hypersaline sites. In an experimental study, Cardona-Olarte et al [16] did not find differences in WUE based on gas exchange of seedling grown in nutrient solutions with salinities between 10 and 40 ppt; however, PNUE decreased from about 85 μmol/mol N at 10 ppt to nearly 60 at 40 ppt.…”
Section: Water Use and N Use Efficiency In Photosynthesismentioning
confidence: 90%
See 1 more Smart Citation
“…However, those differences disappear if the amount of N invested in glycinebetain is subtracted from the total amount of N. In both species, the NUE decreases in hypersaline sites. In an experimental study, Cardona-Olarte et al [16] did not find differences in WUE based on gas exchange of seedling grown in nutrient solutions with salinities between 10 and 40 ppt; however, PNUE decreased from about 85 μmol/mol N at 10 ppt to nearly 60 at 40 ppt.…”
Section: Water Use and N Use Efficiency In Photosynthesismentioning
confidence: 90%
“…Photosynthesis decreases significantly with salinity of interstitial water in several mangrove species [7][8][9][10][11]. Some species appear to be more sensitive to soil salinity than others, a characteristic that may be associated with specific metabolic and structural properties such as synthesis of compatible solutes, root permeability, salt excretion, and compartmentation of excess ions [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although mangrove species are tolerant to flooded conditions, they are still susceptible to flooding damage if plants become completely submerged for days to weeks (Wanless 1998, Mendelssohn and McKee 2000, McKee 2011). Inundation stress typically decreases plant carbon uptake and storage, due to interactions between inundation duration and mangrove transpiration rates; hence A net and growth rates are usually depressed in mangrove forests subjected to longer flooding duration (He et al 2007, Cardona-Olarte et al 2013). For example, greenhouse studies have revealed a 20% reduction in maximum A net when mangrove seedlings and saplings were subjected to short-term intermittent seawater flooding (6 to 22 days, Krauss et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not completely understood how the interaction between water level dynamics and salinity affect in situ rates of leaf gas exchange of mangrove in this region. Experimental evidence using R. mangle seedlings from south Florida showed that inundation created a greater degree of physiological stress than did salinity levels; however, salinity accelerated the adverse effects of inundation stress on leaf function over time (Cardona-Olarte et al 2013). In contrast, other studies have reported no clear effect of water levels or flooding duration on rates of mangrove gas exchange, although inundation duration decreased variability in leaf gas exchange measurements (Hoppe-Speer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove environments may characterize a physiological challenge for plants because of the salinity and, consequently, highly negative water potentials of soil pore water (Krauss et al, 2008;Cardona-Olarte et al, 2013). Therefore, the main issue to mangrove tree species is the tradeoff between water loss and carbon gain, since water acquisition is more energetically expensive than in non-saline soils (Reef & Lovelock, 2015).…”
Section: Introductionmentioning
confidence: 99%